Modernity In The Frame Of Mullah Authorities In Daudi Bohra Denomination - Zaenal Muttaqin (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2011)
Daudi Bohras as a prominent Shiite Ismaili sect in India has been recognized as a modern Islamic society. Despite their traditional Islamic Shiite custom which is brought up from their ancesto4 yet the people of Bohras have a distinct perspective toward Islam as the way of life. Keywords: modernity, mullah, Daudi Bohra